Some new fixed point results in rectangular metric spaces with an application to fractional-order functional differential equations - Budhia, Lokesh; Aydi, Hassen; Ansari, Arslan Hojat; Gopal, Dhananjay (Nonlinear Analysis: Modelling and Control, 2020)
In this paper, we establish some new fixed point theorems for generalized ϕ–ψ-contractive mappings satisfying an admissibility-type condition in a Hausdorff rectangular metric space with the help of C-functions. In this process, we rectify the proof of Theorem 3.2 due to Budhia et al. [New fixed point results in rectangular metric space and application to fractional calculus, Tbil. Math. J., 10(1):91–104, 2017]. Some examples are given to illustrate the theorems. Finally, we apply our result (Corollary 3.6) to establish the existence of a solution for an initial value problem of a fractional-order functional differential equation with infinite delay.